2017
DOI: 10.7573/dic.212508
|View full text |Cite
|
Sign up to set email alerts
|

Analgesics in the management of behavioral and psychological symptoms of dementia: a perspective review

Abstract: The objective of this review was to assess the efficacy and tolerability of analgesics in reducing behavioral and psychological symptoms of dementia (BPSD) among older adults from published randomized controlled trials (RCTs). A literature search was conducted of PubMed, MEDLINE, SCOPUS, PsycINFO, and Cochrane collaboration databases for RCTs in the English language that evaluated the use of analgesics in reducing the severity of BPSD among older adults. Additionally, references of full-text articles that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In line with other studies, the overall consumption of analgesics and anti-psychotic drugs is high (Tampi, Hassell, Joshi, & Tampi, 2017;Shah, Carey, Harris, DeWilde, & Cook, 2011) and did not change over time. As cultural and environmental factors are associated with the prescription rates of these drug (van der Putten, Wetzels, Bor, Zuidema, & Koopmans, 2014) and psychosocial interventions are effective for reducing the use of antipsychotics (Birkenh€ ager-Gillesse et al, 2018), we expected a reduction of antipsychotic drugs among residents moving to a small-scaled SCU.…”
Section: Discussionsupporting
confidence: 90%
“…In line with other studies, the overall consumption of analgesics and anti-psychotic drugs is high (Tampi, Hassell, Joshi, & Tampi, 2017;Shah, Carey, Harris, DeWilde, & Cook, 2011) and did not change over time. As cultural and environmental factors are associated with the prescription rates of these drug (van der Putten, Wetzels, Bor, Zuidema, & Koopmans, 2014) and psychosocial interventions are effective for reducing the use of antipsychotics (Birkenh€ ager-Gillesse et al, 2018), we expected a reduction of antipsychotic drugs among residents moving to a small-scaled SCU.…”
Section: Discussionsupporting
confidence: 90%
“…Pain is a trigger of distress, yet often overlooked as a contributing factor, and the person is not only left to suffer unnecessarily in pain, but also to be prescribed psychotropic agents to manage their behaviors (28). It has been demonstrated that systematic use of observational pain assessment tools can improve the identification of pain in people with dementia, positively impacting the use of non-pharmacological pain interventions and analgesics (1,29,30) As a result of the program analgesic use improved, with fewer people receiving no analgesics (from 15 to 6%) and more receiving regular plus as-needed analgesics (from 24 to 43%). These changes in analgesic use were associated with improvements in pain relief (31).…”
Section: Discussionmentioning
confidence: 99%
“…Tampi et al (30), in their review reported that that the use of analgesics appeared be well tolerated and their use was associated with reduction of BPSD. Improvements were observed in social as well as verbal and physical behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate use of analgesia and psychotropic increases the risk of delirium and further deteriorating cognitive function in the elderly (Alagiakrishnan & Wiens, 2004), who represent most people living with dementia. Furthermore, in people living with dementia, the effect of analgesic pain management is often viewed in line with the change in their pain‐related behaviours or the behavioural psychological symptoms of dementia (Tampi et al., 2017). In this review, while the use of analgesia for treating pain has its beneficial effects in reducing pain‐related behaviours of dementia, dementia‐related agitation has not changed (Chen & Lin, 2016).…”
Section: Discussionmentioning
confidence: 99%